PENGARUH INTELECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2010-2014 - SAIFULLOH, MOCH (Jurnal Akuntansi AKUNESA, 2016)
This research si to investigate the influence  of intellectual capital on the financial performance and market value of the company . this study also analyze the influence between the component of intellectual capital. this study uses a component of intellectual capital as independent variable, which consists of innovation capital, process capital, human capital, and relational capital. whereas, the the financial performance and market value of the company used in this study as dependent variable.  The companies listed on the indonesian stock exchange (idx) in the period between the years 2010-2014 is used as study samples. data was collected using purposive sampling method. based on these criteria then as many as 10 companies chosen as samples in this study. the analytical tool used was partial least square (pls). The result show (1) innovation capital and process capital ade signficant effect on relational capital, (2) innovation capital has possitive effect on human capital, (3) human capital has no effect to customer capital and market value, but it has positive effect on financial performance of company, (4) custmoer capital has no effect to financial performance and market value of company, (5) financial performance has significant effect to market value of the company.